Tawakkul in the Qur'an as Coping Mechanism for IIUM Student Mastery in Coping with the Covid-19 Challenges - Alhafiza, Rahma Ghania; Hanum, Sarmida; Funun, Fatima (Universitas Islam Negeri Imam Bonjol Padang, 2022)
It is a known fact that Covid-19 has affected all academic activities including at the International Islamic University Malaysia (IIUM). There were many implications on students’ academic affairs, mental health, finance, etc. In such a situation, tawakkul as a coping mechanism plays a significant part, as it can define one’s capability in coping with the challenges due to Covid-19 and some tests from Allāh. This study analysed the perception of Hamka on Qur´ānic verses related to tawakkul. It also looked at how IIUM students dealt with challenges brought on by Covid-19. This study employed a qualitative research method in collecting and analyzing data through semi-structured interviews. The findings showed that tawakkul as a coping mechanism according to Hamka refers to having strong imān to overcome painful or difficult emotions. When tawakkul is considered as a coping mechanism, it appeared that it has a very considerable overlap and can be applied for the purpose of assisting one to live a better life. This is due to the fact that practicing tawakkul as coping mechanisms will assist one in overcoming painful or difficult emotions. The findings also revealed that all of the respondents believed that tawakkul was immensely helpful in coping with the challenges they faced during the COVID-19 pandemic